2023
DOI: 10.1002/jcsm.13384
|View full text |Cite
|
Sign up to set email alerts
|

The barriers to interprofessional care for cancer cachexia among Japanese healthcare providers: A nationwide survey

Tateaki Naito,
Hidetaka Wakabayashi,
Sakiko Aso
et al.

Abstract: BackgroundCancer cachexia is a severe complication of advanced malignancy, with few therapeutic options. To promote interprofessional care for cancer cachexia, healthcare providers' needs should be addressed in detail. This pre‐planned subgroup analysis of the Global Educational Needs Evaluation: a systemic interprofessional study in cancer cachexia (GENESIS‐CC) survey aimed to identify barriers to interprofessional care of cancer cachexia in Japan.MethodsA nationwide survey was electronically conducted for he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…To work well, MDT approach to care of a complex disease or syndrome like CC require investment in education, team practice mentorship and training to improve knowledge and shape positive perception. Interestingly, in Japan, a nationwide electronic survey of multi-disciplinary oncological and general healthcare providers (physicians, nurses, pharmacists, dietitians, rehabilitation therapists and other health professionals) indicated that education, team practice, knowledge and perception on CC management were the main barriers to interprofessional care of CC among the HCPs [ 27 ]. Thus, a call for a deliberate institutional effort to nurture team practice, knowledge improvement and building a positive perception of CC syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…To work well, MDT approach to care of a complex disease or syndrome like CC require investment in education, team practice mentorship and training to improve knowledge and shape positive perception. Interestingly, in Japan, a nationwide electronic survey of multi-disciplinary oncological and general healthcare providers (physicians, nurses, pharmacists, dietitians, rehabilitation therapists and other health professionals) indicated that education, team practice, knowledge and perception on CC management were the main barriers to interprofessional care of CC among the HCPs [ 27 ]. Thus, a call for a deliberate institutional effort to nurture team practice, knowledge improvement and building a positive perception of CC syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…A recent global survey of healthcare provider education needs for cancer cachexia (GENESIS-CC) found that only one-third of respondents felt confident in caring for patients at risk of or with cancer cachexia. 3 Subsequent Japanese subgroup analysis 4 revealed large interprofessional differences of barriers in all domains of confidence, knowledge, perception, practice, and education, with pharmacists and nurses having the greatest barriers to cachexia care. Based on this situation, this Asia-Pacific Journal of Oncology Nursing (APJON) special issue focused on multidisciplinary care to shed light on the unmet needs in cancer cachexia care.…”
mentioning
confidence: 99%
“…However, education about cancer cachexia is inadequate in current nursing education. 3 , 4 It is essential to establish an education system for nurses regarding cancer cachexia and to introduce new educational models, including the Human Response to Illness Model presented by McClement. 9 …”
mentioning
confidence: 99%